1966
DOI: 10.1017/s0022112066001095
|View full text |Cite
|
Sign up to set email alerts
|

Flow through a rapidly rotating conduit of arbitrary cross-section

Abstract: The problem of flow through rotating channels of almost arbitrary cross-section is considered. It is shown that when the ratio of the Rossby number and the Reynolds number is small (ε = Ro/Re [Lt ] 1) and when the Reynolds number is not too large (Re [Lt ] ε−1): (1) the viscous effects are important only in thin boundary layers along the channel walls; (2) the flow in the interior is geostrophic; and (3) the inertia effects may be neglected everywhere. Solutions for the geostrophic region and the bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…Benton and Boyer [10] have shown that when the rotational speed is higher and the Reynolds number is small, the inertia effects can be neglected everywhere. If the terms in the left hand side of (16) are ignored, then we have in the frictionless core…”
Section: Remarks On Laminar Flow In Rotating Straightmentioning
confidence: 99%
See 1 more Smart Citation
“…Benton and Boyer [10] have shown that when the rotational speed is higher and the Reynolds number is small, the inertia effects can be neglected everywhere. If the terms in the left hand side of (16) are ignored, then we have in the frictionless core…”
Section: Remarks On Laminar Flow In Rotating Straightmentioning
confidence: 99%
“…A somewhat different approach to the problem has been adopted by Jones and Walters [9], but their results were only of qualitative nature, because the actual secondary flow was replaced by a uniform stream in the plane of cross section of the pipe. Recently Benton and Boyer [10] have analyzed the laminar flow in a rotating straight pipe based on the boundary layer concept, but their theory was confined to a range of high rotational speed and small Reynolds number. Very recently, independently of the authors, Mori and Nakayama [11] have studied the laminar convective heat transfer in a rotating straight pipe by assuming velocity and temperature boundary layers along the pipe wall.…”
Section: Introductionmentioning
confidence: 99%
“…The results for the normal fluid solution are qualitatively the same as for classical rotating pipe flow. 19 In such a case, an element of normal fluid executes a counterclockwise, spiral-like motion in the upper half of the channel and a clockwise spiral in the lower half of the channel. The profile of the x component of the normal fluid velocity appears to be parabolic, but is in fact somewhat flattened due to rotation.…”
Section: Oy Ps Kps Psmentioning
confidence: 99%
“…By including the effects on the normal fluid, one obtains the separate pressure and temperature gradient contributions to Vbe. In the absence of vortex curvature, the equations of motion in the rotating coordinate system are dvs Ps--~ = -OSVP +psS VT-2p, f~ x v~ +F P (18) dr,., -P"Vp-ps$ VT-2p,~12xvn +n[V2v,, + 89 v.)]-F p,.,--~-= p where F is the mutual friction force given by (19) and o~ = t7 • Vs + 211. The equations have been written for a point on the axis of rotation, so that the centripetal acceleration is zero.…”
mentioning
confidence: 99%
“…Because of the existence of the two-body forces, centrifugal flows can become quite complex. Macroscale flows in rotating channels have been investigated experimentally by Benton and Boyer [17], and Ram [18], theoretically by Baura [19] and Benton [20], and numerically by Yang and Kim [21], and Lei and Hsu [22]. Lei and Hsu [22] defined two dimensionless numbers: the rotational Reynolds number, R x (= x a 2 /m, where x, a, and m are the angular velocity of rotation, the characteristic size of the channel and the kinematic viscosity of the fluid, respectively), and the reduced pressure gradient, G (= G * a 3 / q m 2 , where G * is the reduced pressure gradient and q is the Figure 1.…”
Section: Introductionmentioning
confidence: 99%